CHILDHOOD AUTISM SPECTRUM DISORDER – DOLPHIN THERAPY IMPACT ON SENSORY AND MOTOR NERVES OF CHILDREN AUTISM - Prayoga, Septiandi (Journal of Ultimate Public Health, 2017)
The idea that human interaction with dolphins may be beneficial was first formulated in the 1960s by John Lilly, who studied dolphin-human communication and suggested that dolphins could help humans learn to communicate better with one another. Lilly's ideas were extended into the 1970s when dolphin researchers began examining the effects that interacting with dolphins appeared to have on children with neurological impairments (1). The choice of dolphins for this interaction program with ASD children and many other such programs has been based on a number of factors namely: positive image of these animals in the general population (big, protective, friendly aquatic mammals, intelligent and communicative); curious, easily and willingly trainable; capable of sustaining complex interaction with humans when properly condi-tioned; general cooperative and playful attitude; accepting physical contact, including hugs, caresses and kisses; non-threatening expression; soft skin, and delicate movements. These factors have been suggested as useful, in facilitating the establishment of their relationships with humans, with possible therapeutic effects in children (2).